Pengaruh Kompensasi Pada Lingkungan Kerja Terhadap Motivasi Kerja Karyawan PT. Bank Syariah Indonesia, Tbk KCP Pangkalan Brandan - Juliana, Nada; Yusri, Diyan (Universitas Muhammadiyah Sumatera Utara, 2023)
The research aims to determine the effect of compensation on the work environment on the work motivation of employees of PT. Bank Syariah Indonesia, Tbk KCP Pangkalan Brandan. The data source for this research was obtained from the answers to the questionnaire given by the research respondents, namely all employees at PT. Bank Syariah Indonesia, Tbk KCP Pangkalan Brandan. Data analysis in this study used validity test, reliability test, normality test, hypothesis test, and multiple linear regression analysis. Based on this test it is explained that compensation has a significant effect on the work motivation of employees of PT. Bank Syariah Indonesia, Tbk KCP Pangkalan Brandan. This was obtained through the results of hypothesis testing, namely the t test which showed a significant value less than 0.05 or (0.00 0.05) and tcount ttable (4.563 2.10092) so that there was an effect of variable X on variable Y. The compensation given by PT. Bank Syariah Indonesia, Tbk KCP Pangkalan Brandan affects work motivation by 51.1%, while the remaining 48.9% (100% - 51.1%) is influenced by other variables such as education, experience, work discipline, work ability, etc. There is a positive or parallel relationship between Compensation (X) and Work Motivation (Y), the better the Compensation given by PT. Bank Syariah Indonesia, Tbk KCP Pangkalan Brandan, work motivation is also getting better, and vice versa if the compensation given by PT. Bank Syariah Indonesia, Tbk Pangkalan Brandan KCP is bad, so employee performance will also decrease.